Comparison of Examinees’ and Doctors’ Judgement of Health Status Using Data in an AMHTS - Sekita, Y.; Ohta, T.; Inoue, M.; Takeda, H. (Methods of Information in Medicine, 1984)
Judgements of examinees’ health status by doctors and by the examinees themselves are compared applying multiple discriminant analysis. The doctors’ judgements of the examinees’ health status are studied comparatively using laboratory data and the examinees’ subjective symptom data.This data was obtained in an Automated Multiphasic Health Testing System. We discuss the health conditions which are significant for the judgement of doctors about the examinees. The results show that the explanatory power, when using subjective symptom data, is fair in the case of the doctors’ judgement. We found common variables, such as nervousness, lack of perseverance etc., which form the first canonical axis.
Keywords: Judgement of Health Status; AMHTS; Subjective Symptoms; Laboratory Data; Multiple Discriminant Analysis